2021
DOI: 10.1111/cdev.13510
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Neural Synchrony During Father–Child Problem Solving: An fNIRS Hyperscanning Study

Abstract: Interpersonal neural synchrony (INS) has been previously evidenced in mother-child interactions, yet findings concerning father-child interaction are wanting. The current experiment examined whether fathers and their 5-to 6-year-old children (N = 66) synchronize their brain activity during a naturalistic interaction, and addressed paternal and child factors related to INS. Compared to individual problem solving and rest, fatherchild dyads showed increased INS in bilateral dorsolateral prefrontal cortex and lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 64 publications
(142 reference statements)
2
79
1
Order By: Relevance
“…In the current data set, we chose to focus on the analysis of HbO only, for both brevity and its consistent association with neural synchronization (e.g., [25,36,38]). However, we recommend repeating all analyses for HbR (and ideally Hb total) to derive a comprehensive picture of all possible neural synchronization processes [41].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the current data set, we chose to focus on the analysis of HbO only, for both brevity and its consistent association with neural synchronization (e.g., [25,36,38]). However, we recommend repeating all analyses for HbR (and ideally Hb total) to derive a comprehensive picture of all possible neural synchronization processes [41].…”
Section: Discussionmentioning
confidence: 99%
“…fNIRS was simultaneously measured in both participants in bilateral temporo-parietal junction (left hemisphere: Channel 9-12; right hemisphere: Channel 13-16) and dorsolateral prefrontal cortex (left hemisphere: Channel 1-4; right hemisphere: Channel 5-8; see Figure 1B). For a full description of the study design, please refer to [25,26].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same year, Nguyen et al ( 2020c ) tried to extend such results to father-child social interactions. The authors observed neural synchronization between fathers and children's brains in bilateral dorsolateral prefrontal cortex and the left temporo–parietal junction during cooperation.…”
Section: Discussionmentioning
confidence: 99%